1993
DOI: 10.1007/bf01309667
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity of Hantaan virus nucleocapsid and envelope protein studied using baculovirus-expressed proteins

Abstract: Recombinant Hantaan virus nucleocapsid protein (rNP) and recombinant envelope (rEnv) proteins were prepared using a baculovirus expression system to examine the role of Hantaan virus structural proteins in protective immunity. Passive transfer of spleen cells from mice immunized with rNP conferred partial protection or prolongation of time to death from fatal Hantaan virus infection in suckling mice which were challenged with Hantaan virus at 40 LD50 (survival rate: 43%) or 4 LD50 (survival rate: 43%). The T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 31 publications
2
29
0
4
Order By: Relevance
“…SCID mice died 32 to 34 days p.i., while newborn mice usually died within 3 weeks p.i. [25,26,28]. In addition, nervous symptoms such as paralysis and hyperreactivity which are characteristically observed in moribund newborn mice, was uncommon among SCID mice.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…SCID mice died 32 to 34 days p.i., while newborn mice usually died within 3 weeks p.i. [25,26,28]. In addition, nervous symptoms such as paralysis and hyperreactivity which are characteristically observed in moribund newborn mice, was uncommon among SCID mice.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we inoculated hantaviruses to severe combined immunodeficiency (SCID) mice and compared collected for virus isolation and their homogenate was inoculated into Vero E6 cell monolayer as previously described [28]. Various organs were also examined for existence of viral antigen by immunohistochemical procedures as previously described [9,11].…”
Section: Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand infection experiments with suckling mice suggest that N protein-reactive antibodies may confer at least some protection and prolong survival. 37 The humoral immune response towards hantaviruses is longlasting. Several studies have shown that in HCPS-convalescent individuals neutralizing IgG antibodies persist at high levels for years.…”
Section: Human Adaptive Immune Responses To Hantavirusesmentioning
confidence: 99%
“…Although limited efficacy has been observed, attempts have been made to develop recombinant protein-based vaccines that reduce or eliminate biohazard risks during preparation as well as achieve higher efficacy. Immunizations with recombinant G1 and G2 proteins expressed by baculovirus and vaccinea virus induce very low or negligible amounts of neutralizing antibody [12][13][14]. Although the antibody titers are high, this low efficacy for inducing neutralizing antibody may be attributable to the incorrect conformation of the recombinant G1 and G2 compared to the native proteins.…”
Section: Introductionmentioning
confidence: 99%